2020
DOI: 10.1161/strokeaha.119.027230
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Functional Outcomes After Acute Ischemic Stroke

Abstract: Background and Purpose— Smoking is an established risk factor for stroke; however, it is uncertain whether prestroke smoking status affects clinical outcomes of acute ischemic stroke. This study aimed to elucidate the association between smoking status and functional outcomes after acute ischemic stroke. Methods— Using a multicenter hospital-based stroke registry in Japan, we investigated 10 825 patients with acute ischemic stroke hospitalized between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 27 publications
1
33
2
Order By: Relevance
“…On average, smoking may cause stroke people to get stroke 11 years earlier than nonsmokers, resulting in longer periods of disability and suffering. Smoking has also been associated with an elevated risk of unfavorable functional outcomes at 3 months after acute ischemic stroke [66]. Our analysis did not reveal a significant association between smoking and prognosis in posterior circulation stroke patients after MT.…”
Section: Discussioncontrasting
confidence: 62%
“…On average, smoking may cause stroke people to get stroke 11 years earlier than nonsmokers, resulting in longer periods of disability and suffering. Smoking has also been associated with an elevated risk of unfavorable functional outcomes at 3 months after acute ischemic stroke [66]. Our analysis did not reveal a significant association between smoking and prognosis in posterior circulation stroke patients after MT.…”
Section: Discussioncontrasting
confidence: 62%
“…Similar results were reported recently in the Taiwan Stroke Registry, which included approximately 89,000 subacute stroke cases [ 7 ]. This highlights the importance of the so-called index-event-bias [ 16 , 17 ] of smokers due to their lower clinical risk profiles, particularly with respect to age.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple risk factors was found to be the other important predictor of the occurrence of complications and functional outcome as assessed by multivariate logistic regression analysis. There are several studies which have shown that the presence of risk factors like hypertension, diabetes, smoking, and even aging all portend a poorer prognosis in stroke [16][17][18][19][20][21][22][23][24][25][70][71][72][73][74]. Most of our patients had multiple risk factors, suggesting that the presence of more than one risk factor worsens prognosis in stroke.…”
Section: Discussionmentioning
confidence: 63%
“…Most of the traditional risk factors for stroke such as diabetes, hypertension, smoking, and heart disease are prevalent in this region [2]. These aforesaid associated co-morbidities hinder post-stroke recovery and increase complications after stroke [16][17][18][19][20][21][22][23][24][25]. However, several complications can arise as a direct result of the brain-insult itself, from the ensuing disability or immobility, or even from stroke-related treatments [26].…”
Section: Introductionmentioning
confidence: 99%